(untitled) (CIPEEX, 2022)
ABSTRACT CROHN’S DISEASE IS A CHRONIC INFLAMMATORY BOWEL DISEASE THAT AFFECTS THE DIGESTIVE TRACT WITH AN ETIOLOGY THAT IS NOT WELL DEFINED, AND THE ONSET OF THIS DISEASE INVOLVES GENETIC AND ENVIRONMENTAL FACTORS, ALTERED INTESTINAL MICROBIOTA AND ABNORMAL IMMUNITY. THIS CONDITION IS CHARACTERIZED BY ABDOMINAL PAIN, PERSISTENT DIARRHEA, FEVER AND WEIGHT LOSS. THE TREATMENT REQUIRES THE USE OF CORTICOSTEROIDS, IMMUNOSUPPRESSANTS AND BIOLOGICAL THERAPY, AND THE DIAGNOSIS IS BASED ON CLINICAL DATA AND COMPLEMENTARY EXAMS, MAINLY COLONOSCOPY. THIS ARTICLE IS BASICALLY A CASE STUDY WHICH INTENDS TO REPORT THE EXPERIENCE OF A PATIENT LATELY DIAGNOSED WITH CROHN’S DISEASE. THE PATIENT IS A 40-YEAR-OLD FEMALE, WHO PRESENTED CLINICAL COMPLICATIONS THROUGHOUT THE EVOLUTION OF THE DISEASE, SUCH AS EXTRAINTESTINAL MANIFESTATIONS, TOTAL COLECTOMY, MUSCLE LOSS AND WEIGHT LOSS. FURTHERMORE, THE PATIENT GOT PREGNANT, WHICH OBLIGATED HER INTERRUPT THE TREATMENT. THE STUDY ALSO DEMONSTRATED THE CLINICAL IMPROVEMENT AND THE INCREASED OF PATIENT’S QUALITY OF LIFE AS A RESULT OF THE CONTINUOUS USE OF PROBIOTICS, LOPERAMIDE (3 TIMES A DAY) FOR DIARRHEA, VEDOLIZUMADE (EVERY 4 WEEKS) AND METRONIDAZOLE 400 MILLIGRAMS. BECAUSE OF THESE OBSERVATIONS, CD€™S COMPLICATIONS WAS RELATED TO A LATE DIAGNOSIS, WHICH INCREASES THE NUMBER OF EMERGENCY SURGERIES AND POSTOPERATIVE COMPLICATIONS AND WORSEN THE QUALITY OF LIFE. IN ADDITION, IT WAS EVIDENT THAT CD€™S CAN CAUSE INFERTILITY, BUT DOES NOT HAVE HARMFUL EFFECTS DURING THE PREGNANCY.